The Determinants Affecting Irregular Tuberculosis Treatment At Rsu Royal Prima Medan - Telaumbanua, Rizky Anditino; Ginting, Chrismis Novalinda; Nasution, Sri Wahyuni (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
Abstract. Tuberculosis (TB) remains a major public health issue, and irregular treatment adherence is one of the main challenges in controlling the disease. Irregular TB treatment can lead to drug resistance, prolonged illness, and increased transmission rates. Understanding the determinants affecting irregular TB treatment is crucial to improving patient adherence and treatment outcomes. This paper described aims to identify and analysed the factors influencing irregular pulmonary TB treatment at RSU Royal Prima Medan. A descriptive-analytical study was conducted using a cross-sectional approach. Data were collected through patient interviews and medical record reviews. Factors assessed included patient knowledge, socioeconomic conditions, accessibility to healthcare services, side effects of medication, and healthcare provider support. The findings indicate that irregular TB treatment is influenced by several key factors, including lack of patient awareness about the importance of completing treatment, financial constraints, difficulties in accessing healthcare facilities, adverse drug reactions, and inadequate support from healthcare providers. Among these, socioeconomic factors and side effects of medication were found to be the most significant determinants. Addressing the determinants of irregular TB treatment requires a comprehensive approach, including patient education, financial assistance programs, improved healthcare accessibility, and enhanced healthcare provider engagement. Strengthening these aspects can help improve treatment adherence and overall TB control efforts.